Activity of Lactobacillus plantarum on the fermented anchoita (Engraulis anchoita) preservation - Carbonera, Nádia (2010)
Anchoita (Engraulis anchoita) was used to prepare a fermented product with sensorial quality and food safety. A mixture (fish, NaCl, glucose) was employed to evaluate the factors which help to speed up the lactic fermentation, pH decrease and lactic bacteria multiplication, and reducing the deteriorant microorganisms. At first, the viable aerobic bacteria counts were 7.1 Log CFU g-1; thereafter an increase in counting was observed until the 7th day of fermentation which gradually decreased to 6.2 Log CFU g-1until the end of the process (28th day) when 1.5% NaCl and 6.0% glucose were added. The lactic acid bacteria predominated over the deteriorant microorganisms during the whole fermentation period at one logarithmic cycle. The glucose was quickly fermented, although the pH decreased (3.9) slowly for the fish supplemented with 6% glucose and 1.5% NaCl. The total titratable acidity (% lactic acid) after 28 days of fermentation came to 3.7% and 3.4%, when 6.0% and 4% of glucose were added. The inoculation of Lactobacillus plantarum maintained the microbiological quality of the product; the deteriorant bacteria decreased significantly.